The unknown third – Hydrogen isotopes in tree-ring cellulose across Europe - Neil Loader (Science of The Total Environment, 2022)
This is the first Europe-wide comprehensive assessment of the climatological and physiological information recorded by hydrogen isotope ratios in tree-ring cellulose (δ2Hc) based on a unique collection of annually resolved 100-year tree-ring records of two genera (Pinus and Quercus) from 17 sites (36°N to 68°N). We observed that the high-frequency climate signals in the δ2Hc chronologies were weaker than those recorded in carbon (δ13Cc) and oxygen isotope signals (δ18Oc) but similar to the tree-ring width ones (TRW). The δ2Hc climate signal strength varied across the continent and was stronger and more consistent for Pinus than for Quercus. For both genera, years with extremely dry summer conditions caused a significant 2H-enrichment in tree-ring cellulose.The δ2Hc inter-annual variability was strongly site-specific, as a result of the imprinting of climate and hydrology, but also physiological mechanisms and tree growth. To differentiate between environmental and physiological signals in δ2Hc, we investigated its relationships with δ18Oc and TRW. We found significant negative relationships between δ2Hc and TRW (7 sites), and positive ones between δ2Hc and δ18Oc (10 sites). The strength of these relationships was nonlinearly related to temperature and precipitation. Mechanistic δ2Hc models performed well for both genera at continental scale simulating average values, but they failed on capturing year-to-year δ2Hc variations. Our results suggest that the information recorded by δ2Hc is significantly different from that of δ18Oc, and has a stronger physiological component independent from climate, possibly related to the use of carbohydrate reserves for growth. Advancements in the understanding of 2H-fractionations and their relationships with climate, physiology, and species-specific traits are needed to improve the modelling and interpretation accuracy of δ2Hc. Such advancements could lead to new insights into trees' carbon allocation mechanisms, and responses to abiotic and biotic stress conditions.